2019
DOI: 10.1016/j.cels.2019.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Escalating Threat Levels of Bacterial Infection Can Be Discriminated by Distinct MAPK and NF-κB Signaling Dynamics in Single Host Cells

Abstract: Highlights d Live-cell imaging reveals heterogeneity in host signaling during infection d NF-kB and JNK dynamics vary with bacterial location, pathogenicity, and replication d Activation of JNK is a signature of an escalation in bacterial threat level

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 72 publications
0
25
0
Order By: Relevance
“…Comparing invasion by WT bacteria to invasion by a mutant that is defective for intracellular survival due to disruption of the global regulator of virulence AlgR, we found that the host NF-κB response is stronger in WT-invaded compared to ΔalgR -invaded cells. A recent study showed that high and sustained NF-κB signaling and maximal JNK signaling only occurred in response to live bacteria that were sensed by the host as a threat, as opposed to heat-killed bacteria [ 63 ], suggesting that the relatively muted NF-κB signaling on the part of the host in response to ΔalgR invasion may be because it is not sensing the same threat level as it does from WT bacteria. Paradoxically, while the NF-κB response plays a role in clearing of extracellular bacteria [ 17 ], it appears to be required for intracellular bacterial survival, as its inhibition with IKK inhibitors leads to decreased survival of intracellular WT bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing invasion by WT bacteria to invasion by a mutant that is defective for intracellular survival due to disruption of the global regulator of virulence AlgR, we found that the host NF-κB response is stronger in WT-invaded compared to ΔalgR -invaded cells. A recent study showed that high and sustained NF-κB signaling and maximal JNK signaling only occurred in response to live bacteria that were sensed by the host as a threat, as opposed to heat-killed bacteria [ 63 ], suggesting that the relatively muted NF-κB signaling on the part of the host in response to ΔalgR invasion may be because it is not sensing the same threat level as it does from WT bacteria. Paradoxically, while the NF-κB response plays a role in clearing of extracellular bacteria [ 17 ], it appears to be required for intracellular bacterial survival, as its inhibition with IKK inhibitors leads to decreased survival of intracellular WT bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Innate immune cells use pattern recognition receptors (PRRs), such as Toll-like receptors (TLRs), to detect molecules that are indicative of an infection. A cell line expressing both an NF-κB and a c-Jun N-terminal kinase (JNK) reporter was challenged with increasing levels of immune stimulation, from only LPS to infection with Salmonella typhimirium , allowing for measurements of the cell's signaling response in each case (35). This work showed how an individual cell uses TLR signaling to discriminate similar signals in a variety of different contexts.…”
Section: Dynamic Decoding Of Cellular Informationmentioning
confidence: 99%
“…For example, in a population of cells exposed to S . typhimirium , uninfected cells typically activated only NF-κB, while those cells that were infected with bacteria typically activated both JNK and NF-κB (35).…”
Section: Dynamic Decoding Of Cellular Informationmentioning
confidence: 99%
“…To explore how generally applicable FRA is, we examined responses to cytokines IFN-γ, IL-10, and TNF-α 4,27 . As IFN-γ and IL-10 are implicated in macrophage phenotypic diversity 32 , we used the human monocyte cell line U937, differentiated into macrophage-like cells, and immunostaining to measure responses via nuclear levels of the key signaling effectors, phosphorylated STAT1 for IFN-γ, and phosphorylated STAT3 for IL-10 at 30 minutes after stimulation ( Fig.…”
Section: Logarithmic Dose Responses Are a General Property Of Cytokinmentioning
confidence: 99%
“…For instance, low doses of TNF-α may induce one peak of nuclear factor-κB (NF-κB) signaling activity, whereas higher doses may induce additional peaks 7,24 . Besides, the dose may control the onset, shut off, amplitude, or, in principle, any other characteristics of the responses [25][26][27][28] . Overall, conventional dose-response curves do not capture the inherent complexity of single-cell high-throughput data, and an alternative approach is required.…”
mentioning
confidence: 99%